mTOR in podocyte function: Is rapamycin good for diabetic nephropathy? - Lu, Min-Kan; Gong, Xing-Guo; Guan, Kun-Liang (Cell cycle (Georgetown, Tex.), 2011)
Comment on: Inoki K, et al. J Clin Invest 2011; 121:2181-2196 and Gödel M, et al. J Clin Invest 2011; 121:2197-2209